Recognition of Immune Thrombocytopenic Purpura (ITP) through Dental Scaling: A Case Report - Darin Salsabila Hadinda Puteri; Vania Khairunnisa Arianti (Lembaga Penelitian Universitas YARSI, 2025)
Introduction: Immune Thrombocytopenic Purpura (ITP) is a hematologic disorder characterized by low platelet levels (<100.000/µL) and mucocutaneous bleeding involving gingiva. It develops as an antibody-mediated reaction against platelets influenced by genetic, microbial, and drug-related factors. It is more frequently observed in women and children. This case report highlights ITP identification through prolonged gingival bleeding during scaling. Case History: A 46-year-old male patient presented with spontaneous gingival bleeding lasting three days. Intraoral examination showed erythematous and edematous gingival margin with supragingival calculus. The patient experienced prolonged bleeding with delayed coagulation during scaling despite hemostatic gel and 500 mg tranexamic acid per-oral administration. He was referred for complete blood count which revealed severe thrombocytopenia (1.000/µL) and confirmed as ITP. Management involved platelet transfusion and pulse-dose methylprednisolone resulted in improvement of platelet number after 8 months with moon face effect. Discussion: ITP is commonly asymptomatic but dental procedure may uncover its presence through abnormal bleeding. Gingival inflammation from dental plaque accumulation increases vascular permeability that is aggravated by thrombocytopenia resulting in prolonged gingival bleeding even with local hemostatic measures. This condition reflects that he was under severe thrombocytopenic conditions during scaling. Effective plaque control is essential for ITP patients to reduce local inflammation and support systemic stability. Conclusion: Oral manifestation of ITP such as gingival bleeding during scaling emphasizes the pivotal role of general dentists in early detection of hematologic disorders to minimize the risk of further complications.